2022
DOI: 10.3389/fvets.2022.754028
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Analysis of Runs of Homozygosity Islands Affecting Fertility in Mares

Abstract: The loss of genetic variability in livestock populations bred under strict selection processes is a growing concern, as it may lead to increased inbreeding values and lower fertility, as a consequence of the “inbreeding depression” effect. This is particularly important in horses, where inbreeding levels tend to rise as individuals become more and more closely related. In this study, we evaluated the effect of increased inbreeding levels on mare fertility by combining an SNP-based genomic approach using runs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In the last few years, ROHi analysis has been used to examine regions that might be under positive selection across several domesticated species, such as cattle (Peripolli et al, 2018), pigs (Schiavo et al, 2020), sheep (Mastrangelo et al, 2017), horses (Laseca et al, 2022) and even goats (Cardoso et al, 2018; Signer‐Hasler et al, 2022). Using the same approach, we detected 13 regions located in six different chromosomes in which ROH blocks were significantly overrepresented in the whole population, as well as five additional regions (in five different chromosomes) which were only associated with recent inbreeding increases ( F ROH >8 Mb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, ROHi analysis has been used to examine regions that might be under positive selection across several domesticated species, such as cattle (Peripolli et al, 2018), pigs (Schiavo et al, 2020), sheep (Mastrangelo et al, 2017), horses (Laseca et al, 2022) and even goats (Cardoso et al, 2018; Signer‐Hasler et al, 2022). Using the same approach, we detected 13 regions located in six different chromosomes in which ROH blocks were significantly overrepresented in the whole population, as well as five additional regions (in five different chromosomes) which were only associated with recent inbreeding increases ( F ROH >8 Mb).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Casellas et al (2019) and Poyato-Bonilla et al ( 2020) demonstrated, using quantitative data, that individuals with the same F PED can show differences in the onset of inbreeding depression, but also in their capacity to induce inbreeding depression in their offspring (inbreeding depression load). Similarly, studies performed on beef (Pilon et al, 2021), dairy cattle (Martikainen et al, 2018) and mares (Laseca et al, 2022) demonstrated that individuals showing increased homozygosity in specific regions of the genome were more prone to show a decrease in their phenotypic values. In our case, the high levels of variability in the genetic regions with increased inbreeding across the genome fit in with the idea that in some regions increased homozygosity is better tolerated in terms of phenotypic effect.…”
Section: F Roh Variability In Florida Goatsmentioning
confidence: 93%
“…On the other hand, reproductive traits are also influenced by interactions between multiple genes and genetic pathways ( Li et al., 2020 ; Laseca et al., 2022 ), which can make it difficult to identify specific genes or genetic markers associated with globally assessed traits. As a result, the heritability values of reproductive traits are typically lower than those for morphology, conformation, or sport traits.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, the use of an indirect fertility criterion, including precocity and the calving interval, which can be estimated indirectly based on reproductive records, has been demonstrated as an interesting option for selecting more fertile females in extensively-bred livestock species [13,14]. This parameter, called reproductive efficiency (Re), is estimated as the percentage deviation of the number of calvings that a cow has at each age, from the number of calvings that this cow could have had in optimal conditions.…”
Section: Introductionmentioning
confidence: 99%